2019
DOI: 10.7150/jca.29527
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG16 Functions as an Oncogene by Sponging MiR-135a and Promotes JAK2/STAT3 Signal Pathway in Gastric Cancer

Abstract: lncRNA can serve as a miRNA sponge and block the function of miRNA. High expression of lncRNA SNHG16 (small nucleolar RNAhostgene16) was discovered in gastric cancer (GC) and many other tumors. However, the mechanism of SNHG16 in GC is still unclear. In this research, we detected the expression level of SNHG16 in GC tissues and cell lines by qRT-PCR and FISH assay. RIP and Dual Luciferase Reporter Assay revealed that miR-135a is a target of SNHG16. SNHG16 gene knockdown experiment indicated that the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 29 publications
3
61
2
Order By: Relevance
“…For the abnormal regulations between long noncoding RNA (lncRNA) and messenger RNA (mRNA), some studies have shown that lncRNA can promote the proliferation and metastasis of gastric cancer cells by regulating the differentially expressed mRNA. [9][10][11] In recent years, the study have found a new regulatory mechanism called "competitive endogenous RNA (ceRNA)" between the coding RNA and noncoding RNA. 2,4,8 For the relationships of lncRNA-miRNA, although lncRNA and miRNA do not have the function of encoding proteins, the mutual regulations between lncRNA and miRNA can lead to abnormal expression of some signaling pathways and have an important influence on the growth, metastasis, metabolism, and apoptosis of gastric cancer cells.…”
mentioning
confidence: 99%
“…For the abnormal regulations between long noncoding RNA (lncRNA) and messenger RNA (mRNA), some studies have shown that lncRNA can promote the proliferation and metastasis of gastric cancer cells by regulating the differentially expressed mRNA. [9][10][11] In recent years, the study have found a new regulatory mechanism called "competitive endogenous RNA (ceRNA)" between the coding RNA and noncoding RNA. 2,4,8 For the relationships of lncRNA-miRNA, although lncRNA and miRNA do not have the function of encoding proteins, the mutual regulations between lncRNA and miRNA can lead to abnormal expression of some signaling pathways and have an important influence on the growth, metastasis, metabolism, and apoptosis of gastric cancer cells.…”
mentioning
confidence: 99%
“…The experiment was applied to monitor the relative expression of RNA in samples from cells or tissues [22].…”
Section: Quantitative Real-time Pcr (Rt-qpcr)mentioning
confidence: 99%
“…shown that patients with elevated expression of SNHG16 had poor OS in comparison with those with low levels [10][11][12][13][14][15][16][18][19][20][21][22][23][24]. Not only in cancer, recent evidence suggests that SNHG16 also has a significant impact on regulating the inflammatory response.…”
Section: Publication Biasmentioning
confidence: 99%